Diesel exhaust and bladder cancer risk by pathologic stage and grade subtypes. (February 2020) - Koutros, Stella; Kogevinas, Manolis; Friesen, Melissa C.; Stewart, Patricia A.; Baris, Dalsu; Karagas, Margaret R.; Schwenn, Molly; Johnson, Alison; Monawar Hosain, G.M.; Serra, Consol; Tardon, Adonina; Carrato, Alfredo; et al.
Highlights: Risk estimation by quantitative estimates of respirable elemental carbon (diesel) Heavy diesel exhaust exposure was significantly associated with bladder cancer risk. Heterogeneity in the association was observed by stage and grade tumor subtypes. Abstract: Background: The International Agency for Research on Cancer (IARC) classifies diesel engine exhaust as carcinogenic to humans based on sufficient evidence for lung cancer. IARC noted, however, an increased risk of bladder cancer (based on limited evidence). Objective: To evaluate the association between quantitative, lifetime occupational diesel exhaust exposure and risk of urothelial cell carcinoma of the bladder (UBC) overall and according to pathological subtypes. Methods: Data from personal interviews with 1944 UBC cases, as well as formalin-fixed paraffin-embedded tumor tissue blocks, and 2135 controls were pooled from two case-control studies conducted in the U.S. and Spain. Lifetime occupational histories combined with exposure-oriented questions were used to estimate cumulative exposure to respirable elemental carbon (REC), a primary surrogate for diesel exhaust. Unconditional logistic regression and two-stage polytomous logistic regression were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs), adjusting for smoking and other risk factors. Results: Exposure to cumulative REC was associated with an increased risk of UBC; workers with cumulative REC >396 μg/m 3 -years had an OR of 1.61 (95% CI, 1.08–2.40). At this level of cumulative exposure, similar results were observed in the U.S. and Spain, OR = 1.75 (95% CI, 0.97–3.15) and OR = 1.54 (95% CI, 0.89–2.68), respectively. In lagged analysis, we also observed a consistent increased risk among workers with cumulative REC >396 μg/m 3 -years (range of ORs = 1.52–1.93) for all lag intervals evaluated (5–40 years). When we accounted for tumor subtypes defined by stage and grade, a significant association between diesel exhaust exposure and UBC was apparent (global test for association p = 0.0019). Conclusions: Combining data from two large epidemiologic studies, our results provide further evidence that diesel exhaust exposure increases the risk of UBC.